1979
DOI: 10.1126/science.451558
|View full text |Cite
|
Sign up to set email alerts
|

The Forebrain Is Not Essential for Sympathoadrenal Hyperglycemic Response to Glucoprivation

Abstract: The reduction of glycolysis by hypoglycemia or the glucose analog 2-deoxy-D-glucose (2DG) stimulates compensatory sympathetic alterations of metabolism. Considerable attention has been focused on the hypothalamus as the probable locus of requisite metabolic signal detection. We report, however, that unanesthetized chronically decerebrate rats are capable of exhibiting sympathoadrenal hyperglycemia in response to the metabolic challenge presented by 2DG. This findings demonstrates that the forebrain is not nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(64 citation statements)
references
References 52 publications
3
60
0
1
Order By: Relevance
“…In this case, a different population of catecholamine neurons was lesioned which disrupted the sympathoadrenal response to 2DG but left the feeding response intact. The latter result is consistent with a study cited above in which the sympathoadrenal response was observed in decerebrates (44). The abolition of the hyperphagic response to 2DG by DSAP into the PVN is consistent with the suggestion that this structure plays an obligate integrative role, and it is tempting to suggest further that the long-loop mechanism is also important for behavioral response to metabolic signals associated with natural deprivation.…”
Section: Toward An Interpretation Of the Deficient Response To Deprivsupporting
confidence: 92%
See 1 more Smart Citation
“…In this case, a different population of catecholamine neurons was lesioned which disrupted the sympathoadrenal response to 2DG but left the feeding response intact. The latter result is consistent with a study cited above in which the sympathoadrenal response was observed in decerebrates (44). The abolition of the hyperphagic response to 2DG by DSAP into the PVN is consistent with the suggestion that this structure plays an obligate integrative role, and it is tempting to suggest further that the long-loop mechanism is also important for behavioral response to metabolic signals associated with natural deprivation.…”
Section: Toward An Interpretation Of the Deficient Response To Deprivsupporting
confidence: 92%
“…The decerebrate preparation can be used to address the potential for brainstem substrates to effect the same responses in isolation of forebrain influence. Decerebrate rats show a fully formed sympathoadrenal response to systemic 2DG administration (44), indicating that the brainstem contains a complete circuit, including interoceptors responsive to the reduction in utilizable glucose and sufficient integrative machinery to engage a descending command to spinal effectors. The ingestive behavioral response to metabolic inhibitors has not been evaluated.…”
Section: Interoceptor-driven Responsesmentioning
confidence: 99%
“…In addition, injections of 5-thio-glucose in different hypothalamic nuclei failed to induce a glucoregulatory response, whereas its injection into the NTS and the basolateral medulla region containing the A1/C1 catecholaminergic neurons, which project to different sites of the hypothalamus, induced a strong response. [54][55][56] Also, in decerebrated rats, the hyperglycemic response to an intraperitoneal injection of 2-DG is preserved, 57 and c-fos immunostaining revealed that the activated neurons are present in the NTS, the dorsal motor nucleus of the vagus and the catecholaminergic neurons of the basolateral medulla. 58 Thus, hypoglycemia can be detected at several sites, the hepatoportal vein area, the brainstem and the hypothalamus.…”
Section: S64mentioning
confidence: 94%
“…CCK appears required for the ''satiety'' response [155], which also involves neurons in the NTS as well as the dorsomotor nucleus of the vagus (DMV), and is blocked by vagal deafferentiation [156]. In addition to meal size control, decerebrate rats also show a fully formed sympathoadrenal response to systemic 2DG administration [157], indicating that the brainstem houses a complete system responsive to glucoprivation. However, decerebrate rats are not able to increase meal size appropriately in response to food deprivation [158], and, therefore, have an inadequate response to a long-term homeostatic challenge, which requires interactions between hypothalamic and caudal brainstem nuclei [152].…”
Section: The Caudal Brainstem: Autonomic Control Of Eatingmentioning
confidence: 99%